2019
DOI: 10.33545/pathol.2019.v2.i1b.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hematological parameters with peripheral smear in anemia

Abstract: Background: Being one of the most common disorder faced by our society, the correct diagnosis of anemia is important for better clinical outcome. Aim & Objectives: The present study was designed to find out the association between cell counter generated hematological parameters and peripheral smear findings in the diagnosis of anemia. Material and Methods: This study was carried out in a tertiary care hospital in South India. 110 patients with low Hb level with reference to age and sex were selected for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The findings differ from a study conducted by Samly D, et al [31] in which the most common morphological type of anemia was normocytic normochromic anemia in 57.0% of cases. This difference may be due to the difference in the study area; according to Samly D, et al [31] chronic kidney disease and decreased marrow response were the major causes of normocytic normochromic anemia in India and the sample size difference may be another reason for the varation, in the study of Samly D, et al [31] 110 samples were used, which were half of the sample size of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings differ from a study conducted by Samly D, et al [31] in which the most common morphological type of anemia was normocytic normochromic anemia in 57.0% of cases. This difference may be due to the difference in the study area; according to Samly D, et al [31] chronic kidney disease and decreased marrow response were the major causes of normocytic normochromic anemia in India and the sample size difference may be another reason for the varation, in the study of Samly D, et al [31] 110 samples were used, which were half of the sample size of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, in contrast to the PBS examination, the predominant anemia with the findings of the red cell indices obtained from the automated hematological analyzer was normocytic normochromic anemia, which was in 48.0% of cases. These findings were comparable with the study conducted by Samly D, et al [31] in which normocytic normochromic anemia was the predominant anemia, followed by microcytic hypochromic anemia, by the automated hematological analyzer. However, the findings of this research were different from a study conducted by Jain A, et al [28], Singhal S, et al [8], Jansari T, et al [29], Garg M, et al [32], and Ashok C, et al [30] in which microcytic hypochromic anemia was the predominant anemia followed by normocytic normochromic anemia by the result of red cell indices obtained from an automated hematology analyzer.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, it was observed that on peripheral smear study, normocytic normochromic anemia (54.4%) was the most common type followed by microcytic hypochromic anemia, macrocytic anemia, and dimorphic anemia. Similar to the present study, correlated with previous studies conducted by Samly et al,19 61 (55.4%) out of 110 patients had normocytic normochromic anemia, and Agarwal A, 18 40 (40%) out of 100 patients had normocytic normochromic anemia. Normocytic normochromic anemia was the most common type of anemia in the present study, and the most common cause of this was acute and chronic blood loss (►Table 4).…”
Section: Discussionsupporting
confidence: 93%